Enforcement of Underage Marriage Law in Luwu Regency, South Sulawesi - Kahatib, Kamal; Assaad, A. Sukmawati; Nur, Muhammad Tahmid; Gómez, José Manuel Naranjo (IAIN Manado, 2024)
This study aims to examine the enforcement of underage marriage laws in Luwu Regency. This descriptive qualitative study uses a normative-empirical approach to interview, observation, and documentation methods. The results show that the reality of underage marriages in Luwu Regency is influenced by weak public awareness, lack of serious government supervision or education, and factors such as free association, tradition, family economic background, and patriarchal views. Underage marriage practices based on cultural reasons are subject to a criminal penalty of up to 9 years as outlined in Law No. 12 of 2022 on Sexual Violence Crimes, Article 10, Paragraph (1) and (2). The enforcement of underage marriage follows the legal framework of Law No. 16 of 2019, considering the minimum marriage age, and the Supreme Court Regulation No. 5 of 2019 regarding guidelines for adjudicating marriage dispensation requests. Substantively, underage marriage, from a traditional perspective, aims to preserve lineage rather than prioritize material concerns.